2022
DOI: 10.3389/fphar.2022.902054
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Nephrotoxicity of Intravenous Polymyxin B in Carbapenem-Resistant Gram-Negative Bacterial Infections Among Chinese Children

Abstract: Background: No clinical study on the use of polymyxin B in Chinese children has been reported, thus making it difficult for pediatric clinicians to rationally select these drugs.Methods: A retrospective analysis of children treated with polymyxin B during hospitalization in a hospital from June 2019 to June 2021 was conducted to analyze its effectiveness and the incidence of acute kidney injury (AKI) during treatment with polymyxin B.Results: A total of 55 children were included in this study, and the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous retrospective studies evaluating the use of polymyxins in clinical settings reported clinical success rates of approximately 50%. 30,31 In terms of safety, no serious safety signals were identified for ceftazidime-avibactam in our study, whereas adverse effects, particularly nephrotoxicity, were a major concern during polymyxin treatment, with a higher incidence in children. 30,31 The all-cause 30-day mortality rate in our study was 20.0%, which is comparable to that of a recently published retrospective study that included 21 children with hematologic malignancies infected with a carbapenem-resistant gram-negative organism and treated with ceftazidime-avibactam, and reported an overall mortality rate of 20%.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous retrospective studies evaluating the use of polymyxins in clinical settings reported clinical success rates of approximately 50%. 30,31 In terms of safety, no serious safety signals were identified for ceftazidime-avibactam in our study, whereas adverse effects, particularly nephrotoxicity, were a major concern during polymyxin treatment, with a higher incidence in children. 30,31 The all-cause 30-day mortality rate in our study was 20.0%, which is comparable to that of a recently published retrospective study that included 21 children with hematologic malignancies infected with a carbapenem-resistant gram-negative organism and treated with ceftazidime-avibactam, and reported an overall mortality rate of 20%.…”
Section: Discussionmentioning
confidence: 58%
“…30,31 In terms of safety, no serious safety signals were identified for ceftazidime-avibactam in our study, whereas adverse effects, particularly nephrotoxicity, were a major concern during polymyxin treatment, with a higher incidence in children. 30,31 The all-cause 30-day mortality rate in our study was 20.0%, which is comparable to that of a recently published retrospective study that included 21 children with hematologic malignancies infected with a carbapenem-resistant gram-negative organism and treated with ceftazidime-avibactam, and reported an overall mortality rate of 20%. 23 However, the mortality rate of children infected with multidrug-resistant gram-negative organisms and treated with polymyxins in several retrospective reports fluctuated between approximately 30% and 40%, [31][32][33] which is higher than that observed in our study.…”
Section: Discussionmentioning
confidence: 58%
“…Based on the PK/PD characteristics of PMB, it is hypothesized that an appropriate increase in the dose of PMB is beneficial in improving the clinical efficacy of the drug, 32 and the results of existing studies also show that an appropriate increase in the dose of PMB can reduce the all-cause mortality of patients. 29 , 33 The results of our study showed that the bacterial clearance group used high-dose PMB (200 WIU/day) more than the noncleared group, but the multifactorial analysis did not find any therapeutic advantage of high-dose PMB on microbial clearance and all-cause mortality of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective cohort study ( Hasan et al., 2021 ) and a retrospective observational study in China ( Zhou et al, 2021 ) showed that intravenous polymyxin B combined with nebulization therapy resulted in better clinical efficiency and microbial clearance, shortened the extubation time and ICU stay, and reduced the incidence of secondary infections without increasing the risk of renal damage. There are only a few clinical studies on the efficacy and safety of intravenous polymyxin B alone in the treatment of carbapenem-resistant gram-negative bacteria (CR-GNB) pneumonia in children, and these studies showed clinical efficacy rates of 47.8%–53.8%, microbial clearance rates of 30.8%–70.9%, in-hospital mortality rates of 7.3%–32.7%, and incidences of adverse events of 13.5%–27.3% ( Liu et al, 2021 ; Jia et al, 2022 ; Wu et al., 2022 ).…”
Section: Clinical Datamentioning
confidence: 99%